Ki Hadjar Dewantara Thought on Character Education in The Perspective of Islamic Education - Bustomi, Ahmad; Zuhairi, Zuhairi; Basyar, Syaripudin (Tarbawiyah Jurnal Ilmiah Pendidikan, 2022)
This Research aims to describe the thoughts of Ki Hadjar Dewantara on character education in the perspective of Islamic education. This Research is called library research. The data taken in this research consist of primary data and secondary data. The method of data processing uses the analytical descriptive method after the data is collected, classified, compared, interpreted, and finally given the conclusion. The conclusion is made using deductive and inductive patterns. The result of this research shows that character education according to Ki Hadjar Dewantara is the guidance of character in the life of children growing. Character education can be formed through education, experience, life test, sacrifice, and environmental impact. Hereafter the internalized values become an intrinsic value underlying attitude and behavior then repeatedly until becomes a habit, and the habit is guided and maintained then be a character. The method of character education through among method namely momong, among and "ngemong" mean habituation, example, and teaching. Meanwhile, the steps are childhood, the development of souls and thoughts, and the formation of character or social awareness.